A study on prevalence and associated profile of chronic constipation among chronic kidney disease (CKD) patients in hospital USM - Sukri, Muhammad Fakhrullah Mohd (2023)
Chronic constipation is a frequent health concern for chronic kidney disease (CKD) patients. The prevalence of chronic constipation among CKD patients in Hospital USM is still not well recognised. CKD patients are also prone to electrolyte and metabolic abnormalities, increasing the risk of chronic constipation. Therefore, this study aims to explore the prevalence of chronic constipation among CKD patients in Hospital USM using ROME IV functional constipation diagnostic criteria and the Bristol stool form scale. This study also means to look at biochemical profiles associated with chronic constipation in CKD patients. Methodology: A cross-sectional study was conducted among 88 CKD patients (n=88) who received treatment in the nephrology clinic, haemodialysis unit and CAPD clinic Hospital USM from 1st June 2017 till 31st December 2022. Subjects aged 18 and above who fulfilled the inclusion and exclusion criteria were recruited into this study. A guided interview was conducted among the CKD patients using ROME IV functional diagnostic criteria and the Bristol stool form scale. We obtained subjects' average serial blood investigations for at least the last six months (serum urea level, serum calcium, serum magnesium, albumin level and potassium level) from the medical record in Hospital USM. Factor associated with chronic constipation in CKD patients analysed by using multiple logistic regression. Biochemical profile including serum urea level, calcium, magnesium, albumin, and potassium level associated with constipation, analysed by using multiple logistic regression. Result: The prevalence of chronic constipation among CKD patients in Hospital USM using ROME IV functional constipation criteria and Bristol stool form scale was 39.8% (95% CI:2.16,2.93). The most reported stool form type in constipating CKD patients in this study was type 2 stool form (40%). Type 1 stool form written was 26%. The mean of each serum biochemical parameter in constipation and the non-constipation group were almost similar. In CKD patients with constipation, the mean of serum creatinine was 441 (±287), serum urea 16.7 (±8.5), serum potassium 4.3 (±0.64), serum magnesium 0.94 (±0.15), serum calcium 2.16 (±0.17) and serum albumin 33.5 (±6.4). Conclusion: The prevalence of chronic constipation among CKD patients in Hospital USM using ROME IV functional constipation criteria and Bristol stool form scale was 39.8% (95% CI:2.16,2.93), with type 2 stool form was the most reported stool form in constipate group. There is no statistical significance for biochemical analysis associated with chronic constipation among CKD patients in Hospital USM.